WOMEN'S LIVES AFTER BEING DIAGNOSED WITH CERVICAL CANCER - ummu kulsum; Dwi Izzati Budiono; Eighty Mardiyan Kurniawati (UNIVERSITAS AIRLANGGA, 2022)
AbstractBackground: Cancer is the second leading cause of death worldwide after cardiovascular disease. Apart from difficulties in treatment, poor prognosis, and adverse side effects of treatment, cervical cancer also presents psychological challenges for patients. The experience of being diagnosed with cervical cancer is a dramatic event for a woman and causes stress for patient and family For this reason, the exploration of how women with cervical cancer interpret their experiences was deemed important to be investigated in-depth. . Method: This study used a qualitative research design with a phenomenological approach. Data collected by in-depth interviews with 7 participants. Data analysis techniques used are: verbatim, coding, categorization, composing thematic context and data interpretation. Results: This study revealed that the enforcement of cervical cancer diagnosis is always accompanied by psychological challenges, both for patients and their families. After being diagnosed with cervical cancer, participants experienced various changes in all dimensions of their lives, which included changes in daily activities, economic changes, sexual and spiritual activities. Conclusion: Cervical cancer affects and changes all aspects of women's lives and their families, therefore the care given to cervical cancer patients should be carried out holistically